Long-Term Follow-Up of Pediatric Patients Undergoing Hematopoietic Stem Cell Transplantation - Lopes Garcia, Júlia; Vaz de Macedo, Antonio; Dorini Pelegrina, Polliany Roberta; Barbosa Tavares, Rita de Cássia; Vasconcelos Gouveia, Roseane; Seber, Adriana (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
Hematopoietic stem cell transplantation (HSCT) offers the opportunity for cure to patients with malignant and non-malignant diseases. Given the myriad advances in the past few decades, coupled with the rising numbers of transplants worldwide, the number of long-term survivors, many of whom are free of the disease for which they were transplanted, is constantly increasing. Despite the improved prognosis observed overall, long-term outcome may be undermined by transplant-associated morbidity and mortality. Long-term survivors may present a variety of complications, comprising physical, psychological, social, and economic arenas, with a deep impact on quality of life. Therefore, drawing greater attention to and raising awareness of the potential long-term effects of HSCT is key to providing a tailored approach to pretransplant counseling and to devising appropriate recommendations for post-transplant screening, prevention, and timely treatment of secondary events. In 2020, the Brazilian Group for Pediatric Bone Marrow Transplantation of the Brazilian Society for Blood and Marrow Transplantation and Cellular Therapy (SBTMO) convened a task force to provide updated, evidence-based guidance for the long- term follow-up of pediatric patients undergoing HSCT, the results of which are presented here.